DESIGN, SIMULATION, AND IMPLEMENTATION OF AUTONOMOUS TETHERED QUADCOPTER VERTICAL STABILIZATION USING CASCADE PROPORTIONAL, INTEGRAL, AND DERIVATIVE CONTROLLER TUNED WITH PARTICLE SWARM OPTIMIZATION - Leonardi
Autonomous quadcopter is used for many applications, including industrial works, government, and recreational uses. However, many still uses an on-board battery as its power supply therefore limiting the flight duration capability. There’s different methods used to increase the flight duration of an autonomous quadcopter, such as an autonomous battery changing system and the use of tether as means of supplying power. Tethered quadcopter will have a long continuous flight duration, however the usage of tether cable will give extra inertial effects to the quadcopter dynamics. In this work, we designed, simulated, and implemented vertical stabilization to the autonomous tethered quadcopter. The frame used is a true X type. Modelling is done to the extra forces and moments caused by the tether able to simulate the effects of the controller that is designed. PID controller has commonly been used to autonomosly control a quadcopter, in this work we designed a cascade PID controller for the tethered quadcopter. Particle swarm optimization (PSO) algorithm is used to optimize the PID parameters. The resulting parameters then will be tested through the buils simulation environment. The designed controller is then implemented to the built prototype. The use of PSO algorithm to tune the PID parameters is deemed sucesfull, as the particle of the PSO is convergent to the global best solution. The resulting cascade PID controler parameters give a stable flight through simulation although showing a little overshoot on the yaw angle controller. Integration of the control algorithm is done through MAVROS as a high level controller and ArduCopter as a low level controller. Test flights is done indoors. The observers used in the prototype gives bad results except for the vertical observer. The biggest RMSE for the vertical, longitudinal, lateral, and heading axis in sequence are 7.38 cm, 19.49 cm, 26.84 cm, and 2,95 degree. The bad performance of the longitudinal, lateral, and heading axis is caused by mechanical vibration resulting in a noisy IMU reading as well as magnetic interference which causes noise in the magnetometer reading. The position controller of the prototype results in RMSE of 5.3 cm for the vertical position, 27.36 cm for the longitudinal position, and 58.37 cm for the lateral position. Implementation of the autonomous tethered quadcopter is then limited to vertical stabilization.